Fatigue and sleep quality among cancer patients receiving chemotherapy in Hospital Universiti Sains Malaysia - Phey, Cheong Phey (Universiti Sains Malaysia, 2024)
Cancer is a major global issue, and fatigue is one of the most common symptoms experienced by cancer patients. The fatigue experienced by cancer patients differs from that of ordinary people and is influenced by chemotherapy and the disease itself. This study aims to assess the levels of fatigue and sleep quality among cancer patients receiving chemotherapy. A cross-sectional study was conducted at the Day Care Oncology Unit and Oncology Ward at Hospital Universiti Sains Malaysia (Hospital USM) from January to March 2024. A total of 99 respondents were selected using convenience sampling, and data were collected using a self-administered questionnaire. The data were analyzed using descriptive statistics and Pearson's Correlation with the Statistical Package for Social Sciences (SPSS) version 27.0. Pearson's Correlation was used to determine the correlation between fatigue levels and sleep quality among the participants. The results showed that most patients (n=93, 93.9%) had low levels of fatigue and good sleep quality (n=66, 66.7%). Pearson's Correlation indicated a significant correlation between fatigue levels and sleep quality [r= .467, p = .001] among cancer patients receiving chemotherapy at Hospital USM. In summary, the findings of the study can be used as a basis for determining fatigue levels and sleep quality among cancer patients in the Malaysian healthcare setting.